"I Wasn't Sure What It Meant to Be Honest"-Formative Research Towards a Physical Literacy Intervention for Preschoolers - Jonathan D. Foulkes; Lawrence Foweather; Stuart J. Fairclough; Zoe Knowles (MDPI AG, 2020)
Physical literacy (PL) as a concept is important in developing lifelong physical activity; however, there is little research exploring how PL can be developed during the preschool years. This two-phase qualitative study sought the insights of academics/expert practitioners and preschool staff towards PL in order to inform the design of future preschool PL interventions. Phase One comprised of nine semi-structured interviews with experts in the field of children's physical activity and/or PL. Interview topics included perspectives on the concept of PL and recommendations for interventions targeted at improving preschool PL. Phase Two consisted of focus groups with practitioners from four local children's centres. Focus groups explored perspectives on the feasibility and acceptability of proposed PL interventions. Interviews and focus groups were analysed by thematic analysis and means of representation, respectively. Findings revealed that whilst there was limited understanding about the concept of PL among preschool educators, knowledge of child development was evident and that all participants agreed that there was a need for further training for practitioners. Perceived barriers to promoting PL noted by practitioners included funding, policy, curricular priorities, parental opinions, and the preschool environment. It was recommended that interventions should be: (i) designed using a participatory approach including all key stakeholders, (ii) conducted over the long term, and (iii) incorporate opportunities for children to engage in free and outdoor play. Furthermore, any intervention should be flexible to allow for variation between children's centres, aligned to current policy/children's centre targets and provide training and resources in order to overcome perceived barriers.